Epoxy Composites Reinforced with Negative‐CTE ZrW2O8 Nanoparticles for Electrical Applications. Issue 2 (30th May 2012) - Badrinarayanan, Prashanth; Rogalski, Mark; Wu, Hongchao; Wang, Xiaofeng; Yu, Wonjong; Kessler, Michael R.
Abstract The potential for incorporating negative‐CTE zirconium tungstate (ZrW2O8) nanoparticles in an epoxy matrix with the aim of developing epoxy/ZrW2O8 nanocomposites with tailored CTE values for electrical applications is investigated. The ZrW2O8/epoxy nanocomposites are prepared through incorporation of up to 20 vol% unfunctionalized nanoparticles or silane‐functionalized nanoparticles containing either epoxy or amine end groups. Improvements in thermomechanical and dynamic mechanical properties of the epoxy matrix are achived with no detrimental effect on the dielectric strength, which suggests that these nanocomposites could be viable candidates for a wide range of electrical applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>